Analisis Kepastian Hukum dalam Penerapan Diversi terhadap Anak yang Berhadapan dengan Hukum - Andini eka Nur,aziza (Jurnal Hukum Lex Generalis, 2026)
Diversion, as the primary instrument in the juvenile criminal justice system, under Law Number 11 of 2012 aims to achieve restorative justice. This study uses normative juridical methods to analyze the impact of diversion on child development and legal certainty in serious crimes. The results indicate that diversion has a positive impact, but it does not guarantee legal certainty due to differing interpretations and the lack of technical standards. It is recommended that technical guidelines for diversion, standards for juvenile sentencing, improved training for officers and strengthened coordination between institutions be developed to ensure legal consistency.